EDUKASI CUCI TANGAN PAKAI SABUN (CTPS) DENGAN MEDIA BOOKLET DALAM UPAYA PENCEGAHAN INFEKSI COVID 19 PADA SISWA DI MA AL IKHLAS JATINEGARA - ita nur itsna; Anisa Oktiawati; Risnanto Risnanto; Khodijah Khodijah (UNIVERSITAS BHAMADA SLAWI, 2021)
Infection a virus known as coronavirus has hit various countries in the world. Several types of coronavirus are known to cause respiratory tract infections in humans ranging from colds to more serious coughs. The spread of this virus is increasing very rapidly. This is because the virus can spread from person to person through droplets from the nose or mouth that come out when an infected person talks, sneezes, or coughs. One of the efforts to prevent Covid 19 infection is to adopt a clean and healthy lifestyle. The application of clean and healthy living habits in schools is also very important to ensure the health and safety of children while studying during the Covid 19 pandemic. One of the indicators of a Clean and Healthy Life Behavior is “Cuci Tangan Pakai Sabun (CTPS)”. CTPS is one of the sanitation measures by cleaning hands and fingers using soap and water to make them clean. One of the media used in counseling is a booklet containing writing accompanied by pictures. The extension activity was attended by 26 people and began with the delivery of definitions, signs and symptoms, supporting examinations, prevention and treatment and then the practice of washing hands with soap and accompanied by the use of booklet media. The students listened carefully to the sequence of steps described by paying attention to the CTPS steps as listed in the given booklet. The use of booklet media helps in improving the skills of students and teachers and it is hoped that the implementation of CTPS will become a habit in everyday life. Keywords : Cuci Tangan Pakai Sabun (CTPS), Booklet, Covid 19